2019
DOI: 10.2337/dc20-s013
|View full text |Cite
|
Sign up to set email alerts
|

13. Children and Adolescents: Standards of Medical Care in Diabetes−2020

Abstract: The American Diabetes Association (ADA) "Standards of Medical Care in Diabetes" includes the ADA's current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee (https://doi.org/10.2337/dc20-SPPC), are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(127 citation statements)
references
References 222 publications
(45 reference statements)
1
117
0
9
Order By: Relevance
“…Using sphygmomanometry, we found that systolic blood pressure (SBP) was 112.16 mmHg in girls and 119.16 mmHg in boys, whereas diastolic blood pressure (DBP) was 76.08 mmHg for the former, and 76.06 mmHg for the later ( Table 2 and Table S1). These data indicate that vascular pressure was not altered [19]. However, cardiac performance could have been affected.…”
Section: Cardiovascular Complications Associated With T1dmmentioning
confidence: 66%
See 2 more Smart Citations
“…Using sphygmomanometry, we found that systolic blood pressure (SBP) was 112.16 mmHg in girls and 119.16 mmHg in boys, whereas diastolic blood pressure (DBP) was 76.08 mmHg for the former, and 76.06 mmHg for the later ( Table 2 and Table S1). These data indicate that vascular pressure was not altered [19]. However, cardiac performance could have been affected.…”
Section: Cardiovascular Complications Associated With T1dmmentioning
confidence: 66%
“…Similarly, 86.7% of males showed poor glycemic control (HbA1c ≥ 7.5 mg/dL) [19]. Their HbA1c levels were 9.58% (8.98% in the last three years) and FBG was 127.0 mg/dL ( Table 1).…”
Section: Characterization Of the Uncontrolled T1dm Populationmentioning
confidence: 95%
See 1 more Smart Citation
“…The potential increased parental emphasis on the importance of diabetes control, along with the related pressure to engage in healthy eating behaviors and to take control of their weight, seems to be con rmed by the zBMI values (which were found to be lower than those measured in the latest diabetes visit) and by the HbA1c values remaining unchanged. It is worth noting that glycemic control-even though higher than the American Diabetes Association's recommended target value of 7.5% for good metabolic control [58]-is substantially analogous to population data in similar age groups [59,60].…”
Section: Discussionmentioning
confidence: 85%
“…In conclusion, our ndings suggest that, as recommended by international guidelines [12,58,73], continuous medical and psychological care is needed in order to periodically monitor physical and psychological conditions, especially during critical developmental phases, as teens age and/or face troubling circumstances such as those imposed by quarantine.…”
Section: Discussionmentioning
confidence: 91%